2021
DOI: 10.1111/evj.13496
|View full text |Cite
|
Sign up to set email alerts
|

Retrobulbar lidocaine injection via the supraorbital fossa is safe in adult horses but produces regionally variable periocular anaesthesia

Abstract: Background Injection techniques for retrobulbar anaesthesia are published in horses, but neither safety nor anaesthetic efficacy and duration have been evaluated objectively in vivo. Objective To characterise the safety and efficacy of one published technique for retrobulbar anaesthesia. Study design Randomised, controlled descriptive experiment. Methods Unilateral retrobulbar injection with 10 mL lidocaine (2%) was performed in eight sedated adult mares. Contralateral eyes served as untreated controls. Neurop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 40 publications
2
12
0
Order By: Relevance
“…We also found that when the needle is positioned in the region of the globe, there is a risk of inadvertent penetration of the globe and/or nerve injury or anterior spread of the local anesthetic. Anterior spread of the anesthetic may cause chemosis (swelling of the conjunctiva), an undesired effect of the RNB known in clinical practice [ 3 , 20 , 21 ]. In human as well as in equine practice, the prevalence of chemosis after RNB is unknown [ 20 , 22 ], although in a recent in vivo study of blind retrobulbar injections using eight horses, three quarters showed mild to moderate reversible chemosis for 2 to 24 h [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…We also found that when the needle is positioned in the region of the globe, there is a risk of inadvertent penetration of the globe and/or nerve injury or anterior spread of the local anesthetic. Anterior spread of the anesthetic may cause chemosis (swelling of the conjunctiva), an undesired effect of the RNB known in clinical practice [ 3 , 20 , 21 ]. In human as well as in equine practice, the prevalence of chemosis after RNB is unknown [ 20 , 22 ], although in a recent in vivo study of blind retrobulbar injections using eight horses, three quarters showed mild to moderate reversible chemosis for 2 to 24 h [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anterior spread of the anesthetic may cause chemosis (swelling of the conjunctiva), an undesired effect of the RNB known in clinical practice [ 3 , 20 , 21 ]. In human as well as in equine practice, the prevalence of chemosis after RNB is unknown [ 20 , 22 ], although in a recent in vivo study of blind retrobulbar injections using eight horses, three quarters showed mild to moderate reversible chemosis for 2 to 24 h [ 21 ]. Chemosis does not seem to have a long-term effect, but it often interferes with surgical procedures and corneal ulceration can occur postoperatively [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations